RETRACTED ARTICLE: Impact TB co-infections on immune tolerance among people living with HIV: a systematic review - Yimam Getaneh; Siti qamariyah Khairunisa; Dominicus Husada; Kuntaman Kuntaman; Maria Inge Lusida (HIV Research & Clinical Practice)
We, the Editors and Publisher of HIV Research & Clinical Practice, have retracted the following article: Getaneh, Y., Khairunisa, S. qamariyah, Husada, D., Kuntaman, K., & Lusida, M. I. (2023). Impact TB co-infections on immune tolerance among people living with HIV: a systematic review. HIV Research & Clinical Practice, 24(1). https://www.tandfonline.com/doi/full/10.1080/25787489.2023.2270822 Since publication, significant concerns have been raised about the fact that this article has substantial overlap with the following published articles, which have not been cited or referenced: Figure 1 and associated caption in the above article are from Anandaiah A, Dheda K, Keane J, Koziel H, Moore DA, Patel NR. Novel developments in the epidemic of human immunodeficiency virus and tuberculosis coinfection. Am J Respir Crit Care Med. 2011 Apr 15;183(8):987-97. https://www.atsjournals.org/doi/full/10.1164/rccm.201008-1246CI Figure 2 and the associated caption in the above article are from Sharan, R., Bucşan, A. N., Ganatra, S., Paiardini, M., Mohan, M., Mehra, S., Khader, S. A., & Kaushal, D. (2020). Chronic Immune Activation in TB/HIV Co-infection. Trends in Microbiology, 28(8), 619-632. https://doi.org/10.1016/j.tim.2020.03.015 Significant textual overlap with Walker, N. F., Meintjes, G., & Wilkinson, R. J. (2012). HIV-1 and the Immune Response to TB. Future Virology, 8(1), 57–80. https://doi.org/10.2217/fvl.12.123 Upon query, the author has not been able to provide a satisfactory explanation for this significant level of overlap. As this is a serious breach of our Editorial Policies, we are retracting the article from the journal. The authors do not agree with the retraction. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.